Harmonization of Sharia Values in the Modern Inheritance System: Opportunities, Challenges, and Sustainability - Siti Ropiah (Universitas Ibn Khaldun, 2025)
The Islamic inheritance system is founded on principles aimed at ensuring justice, balance, and sustainability in the distribution of inheritance assets. However, in the modern context, the application of Sharia values in inheritance systems faces various challenges, including social dynamics, changes in family structures, and legal regulations in different countries. This study aims to examine the opportunities and challenges in harmonizing Sharia values with modern inheritance systems and explore strategies for their sustainability. The research method employed is a literature review using normative and comparative approaches, analyzing various inheritance models implemented in both Muslim and non-Muslim countries. The findings indicate that despite obstacles in implementing Islamic inheritance law, there are opportunities through flexible regulations, strengthening Islamic legal literacy, and contextual fatwa adaptations. On the other hand, major challenges include conflicts with positive law, differences in scholars' interpretations, and social resistance to inheritance distribution based on Islamic law. For sustainable implementation, it is essential to develop an inheritance model that not only adheres to Sharia principles but also adapts to modern legal and social realities. Therefore, harmonizing Sharia values within the modern inheritance system requires an inclusive and solution-oriented approach that holistically considers legal, social, and economic aspects. Keywords: Islamic inheritance; Sharia law; Modern inheritance system; Legal harmonization; sustainability.